The challenge of Third World development - Handelman, Howard 1943- (Pearson/Prentice Hall, 2006)
This book explores political, economic, and social issues common to diverse Third World countries. It stresses the themes of democratization, modernization, and dependency theory, examining the nature of underdevelopment. The text analyzes the major political and socio economic rifts that divide many of these nations and the efforts being made to understand and address these challenges.